Camp songs [compact disc] - Jenkins, Ella; Seeger, Anthony; Seeger, Kate; Walz, Chris; Halker, Bucky; Silverman, Barbara (Smithsonian Folkways Recordings, 2017)
Children's performer Ella Jenkins assembled a group of children, parents, and teachers from the Old Town School of Folk Music in Chicago, along with Tony and Kate Seeger from Camp Killooleet, to sing these classic camp songs, rounds, silly songs, and campfire sing-alongs.